A robust numerical method for granular hydrodynamics in three dimensions - Shakeri, Ali; Schiochet Nasato, Daniel; Müller, Patric; Torres Menendez, Harol; Pöschel, Thorsten (Journal of Fluid Mechanics, 2021)
Granular systems are of a discrete nature. Nevertheless, it can be advantageous to describe their dynamics by means of continuum mechanical methods. The numerical solution of the corresponding hydrodynamic equations is, however, difficult. Therefore, previous numerical simulations are typically geared towards highly specific systems and frequently restricted to two dimensions or mild driving conditions. Here, we present the first robust general simulation scheme for granular hydrodynamics in three dimensions which is not bound to the above limitations. The performance of the simulation scheme is demonstrated by means of three applications which have been proven as notoriously difficult for numerical hydrodynamic description. Although, by construction, our numerical method covers grain-inertia flows, the presented examples demonstrate that it produces reliable results even in the jammed or high density limit.
CRIS-Team Scopus Importer:2021-05-14
Keywords: granular media

Granular Leidenfrost effect in microgravity - Torres Menendez, Harol; Sack, Achim; Pöschel, Thorsten (Granular Matter, 2020)
When a container filled with granular material is subjected to vertical vibration in the presence of gravity, under certain conditions a non-monotonous density profile can be observed. This effect which is characteristic for dissipative granular gases, was termed “floating cluster regime” or “granular Leidenfrost effect”. Here, we study the behavior of vibro-agitated granular matter in the absence of gravity and identify a corresponding stationary state of the granulate, that is, we provide experimental evidence of the granular Leidenfrost effect under conditions of weightlessness.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Floating cluster; Granular matter; Leidenfrost effect; Microgravity; Parabolic flight; Weightlessness; X-ray radiography

Lack of collective motion in granular gases of rotators - Torres Menendez, Harol; Altshuler, Ernesto; Brilliantov, Nikolai; Pöschel, Thorsten (New Journal of Physics, 2022)
The dynamics of gases made of particles interacting dissipatively-known as granular gases-can be fully described by the translational and rotational motion of the individual particles; however, most of the results in the field refer to the limit of smooth particles, which implies that the rotational degrees of freedom are suppressed. Here we investigate the opposite limit: we consider a granular gas where the translational degrees of freedom are suppressed, and the key degrees of freedom are rotational. Our results indicate that for many-particle systems of pure rotators collective effects almost completely suppressed. This is in a sharp contrast to granular gases of smooth particles and other conventional matter where the translational degrees of freedom dominate the kinetics.
CRIS-Team WoS Importer:2022-07-15

X-ray tomography in micro-gravity - Torres Menendez, Harol; Heckel, Michael; Sack, Achim; Pöschel, Thorsten (Review of Scientific Instruments, 2019)
We present an X-ray device for use under conditions of weightlessness to produce high-speed radiograms and tomograms. The device is equipped with two detectors of different resolutions, a high temporal resolution-small area detector (4 Mpix within 13 × 13 mm2) and a low temporal resolution-large area detector (3 Mpix within 145 × 115 mm2). Using the high temporal resolution detector, the device achieves a recording rate of up to 25 655 radiograms per second, while using a low temporal resolution detector, up to 86 radiograms can be recorded per second. For the first time, we could record complete X-ray tomograms in microgravity aboard a parabolic flight in 16 s using a laboratory microfocus X-ray source. We demonstrate the operation of the device by analyzing the three-dimensional packing of particles (tomograms) and structure formation in a granular gas under periodic excitation (radiograms).
CRIS-Team Scopus Importer:2019-10-22